Bladder cancer detection using a peptide substrate of the 20S proteasome. (14th July 2016) - Gruba, Natalia; Wysocka, Magdalena; Brzezińska, Magdalena; Dębowski, Dawid; Sieńczyk, Marcin; Gorodkiewicz, Ewa; Guszcz, Tomasz; Czaplewski, Cezary; Rolka, Krzysztof; Lesner, Adam
Abstract : The 20S catalytic core of the human 26S proteasome can be secreted from cells, and high levels of extracellular 20S proteasome have been linked to many types of cancers and autoimmune diseases. Several diagnostic approaches have been developed that detect 20S proteasome activity in plasma, but these suffer from problems with efficiency and sensitivity. In this report, we describe the optimization and synthesis of an internally quenched fluorescent substrate of the 20S proteasome, and investigate its use as a potential diagnostic test in bladder cancer. This peptide, 2‐aminobenzoic acid (ABZ)‐Val‐Val‐Ser‐Tyr‐Ala‐Met‐Gly‐Tyr(3‐NO2 )‐NH2, is cleaved by the chymotrypsin 20S proteasome subunit and displays an excellent specificity constant value (9.7 × 10 5  m −1 ·s −1 ) and a high k cat (8 s −1 ). Using this peptide, we identified chymotrypsin‐like proteasome activity in the majority of urine samples obtained from patients with bladder cancer, whereas the proteasome activity in urine samples from healthy volunteers was below the detection limit (0.5 pm ). These findings were confirmed by an inhibitory study and immunochemistry methods. Abstract : Herein we describe the optimisation and synthesis of fluorogenic peptide of the 20S proteasome, and investigate its use as a potential diagnostic test in bladder cancer. Using this peptide, we identified chymotrypsin‐like proteasome activity in the majority of urine samples obtained from patients with bladder cancer, whereas the proteasome activity in urine from healthy volunteers was below the detection limit.